Transport Phenomena and Evaporation on Interface of Gas-Liquid by Reversed-Flow Gas Chromatography: A Review - Mohammad1, H.H.; Khalid2, Khalisanni; Mohd. Zain1, Sharifuddin (Asian Journal of Chemistry, 2014)
Gas-liquid interface plays a major interest in environmental studies especially when the researchers are interested to study the diffusion coefficients and rate coefficients of the liquid under studies into the chosen carrier gas. The study of the gas-liquid interface by reversed-flow gas chromatography (RF-GC) is based on Ficks first law in one dimensional and Henry's law. Based on the two laws, an extensive works have been done previously by using reversed-flow gas chromatography methodologies to determine physiochemical properties on the gas-liquid interface. The setup for this method is just by modifying the commercial gas chromatography by including diffusion column which orientated right angle to the sampling which carried the carrier gas. The bottom part consists of the glass bottle which holds the liquid under studies. The usage of six-port or four-port valves play a major role in this methodologies since the equipment allows the carrier gas to reverse and retain its original flow from time to time and thus creating a 'sample peak' which sits on the continuous signal versus time chromatogram. The diffusion column which contains stagnant carrier gas accounts for the stationary phase and thus contributes to the physiochemicals phenomena of the interface. This methodology can be considered as fast sampling procedure as compared to the others in term of determining rate coefficients and diffusion coefficients of liquid sample into the carrier gas. The methods not only important in environmental investigation but can also be applied in the area of material science, food chemistry, nanotechnology, biological science and chemical technology.